PELATIHAN PENGELOLAAN MAJALAH DINDING SISWA MA DARUSSALAM BARITO KUALA - Yunus, Muhammad - (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
This training activity aims to train students to manage wall magazines properly. Aside from being a forum to foster student creativity so that they can pour their work both in the field of literature and those related to writing. The method used in this service is counseling through several stages, namely (1) delivery of material (2) Formation of editorial teams and (3) making bulletin boards. With this training students finally know how to manage wall magazines and various stages from the beginning to the end of publishing. Students also finally get a lot of knowledge that they did not know about the management or management of wall magazines at school.